Порiвняльний аналiз цитотоксичностi природних клiтин-кiлерiв у хворих з доброякiсними та злоякiсними пухлинами щитовидної залози до та пiсля лiкування - Захарченко, Т.Ф.; Замотаєва, Г.А.; Тронько, М.Д. (Видавничий дім "Академперіодика" НАН України, 2008)
The authors have studied the cytotoxic activity of natural killer (NK) cells. With this purpose, the NK-cell activity was determined in 49 patients with benign thyroid tumours and in 48 patients with malignant thyroid tumours (aged from 18 to 65 years, 84 women and 56 men) depending upon the age, gender, degree of spreading, and presence of tumour metastases before surgery and in 1 to 6 months after surgery. The control group (43 subjects) consisted of practi- cally healthy persons of appropriate age and gender. In a second series of investigations, the authors have examined 35 patients with papillary thyroid cancer (TC) before prescribing a regular course of radioiodine therapy and 25 patients from this group who had received radi- oiodine therapy for eliminating a residual thyroid tissue and treating metastases. It has been shown that the NK-cell cytotoxic activity in patients with TC did not depend upon the age, but depended to a large extent upon the gender, degree of tumour spreading, and presence of metastases, being the lowest at T4 stage and in the group with metastases. Unlike pati- ents with benign tumours, in patients with papillary TC, the NK-cell activity was significantly suppressed. After surgical treatment of patients with TC, the NK-cell activity was decreased by 1.5 times as compared to that in healthy donors. After radioiodine therapy, the NK-cell activity in patients with papillary TC was additionally decreased by 1.3 times as compared to the initial indicator.